Effects of COVID-19 on the economy and mental health of young people in South Africa: opportunities for strengthening social protection programmes by integrating mental health. (June 2021) - Álvarez-Iglesias, Alejandra; Garman, Emily; Lund, Crick
The majority of COVID-19 cases in sub-Saharan Africa are found in South Africa, where one third of young people are not in employment, education or training. As the world continues to fight the COVID-19 virus spread, an increasing volume of studies are analysing and trying to predict the consequences of the pandemic on the economy and on physical and mental health. This article describes the economic and psychological impact of COVID-19 in South Africa's youth specifically, the efforts made to tackle these issues, and the opportunities to integrate mental health into the country's social protection measures, such as the Child Support Grant.